Spectrophotometric Estimation of Clarithromycin in Pharmaceutical Formulations - Seshagiri Rao, J.V.L.N.; Srinivasa Rao, Y.; Murthy, T.K.; Sankar, D.G. (Asian Journal of Chemistry, 2010)
Two simple and sensitive spectrophotometric methods A and B have been developed for the estimation of clarithromycin in pure and pharmaceutical dosage forms. Method A is based on the reaction of the drug with iron(III) and a subsequent reaction with potassium ferricyanide to yield a prussian blue coloured product with a maximum absorption at 740 nm. In method B, the drug forms a blue coloured complex with Folin-Ciocalteu reagent, showing maximum absorption at 775 nm. The methods obey Beer's law in the concentration range of 12.5–75.0 μg/mL (method A) and 250–125.0 μg/mL (method B). The common excipients used as additives in tablets do not interfere with the proposed methods. Analytical data for determination of the pure compound are presented together with the applications of the proposed methods to the analysis of some tablets. The methods have been statistically evaluated and are found to be precise and accurate.